IFN-γ–Mediated Induction of an Apical IL-10 Receptor on Polarized Intestinal Epithelia - Douglas J. Kominsky; Eric L. Campbell; Stefan Ehrentraut; Kelly Wilson; Caleb Kelly; Louise Glover; Colm B. Collins; Amanda J. Bayless; Bejan Saeedi; Evgenia Dobrinskikh; Brittelle Bowers; Christopher F. MacManus; et al. (2013)
Cytokines secreted at sites of inflammation impact the onset, progression, and resolution of inflammation. In this article, we investigated potential proresolving mechanisms of IFN-γ in models of inflammatory bowel disease. Guided by initial microarray analysis, in vitro studies revealed that IFN-γ selectively induced the expression of IL-10R1 on intestinal epithelia. Further analysis revealed that IL-10R1 was expressed predominantly on the apical membrane of polarized epithelial cells. Receptor activation functionally induced canonical IL-10 target gene expression in epithelia, concomitant with enhanced barrier restitution. Furthermore, knockdown of IL-10R1 in intestinal epithelial cells results in impaired barrier function in vitro. Colonic tissue isolated from murine colitis revealed that levels of IL-10R1 and suppressor of cytokine signaling 3 were increased in the epithelium and coincided with increased tissue IFN-γ and IL-10 cytokines. In parallel, studies showed that treatment of mice with rIFN-γ was sufficient to drive expression of IL-10R1 in the colonic epithelium. Studies of dextran sodium sulfate colitis in intestinal epithelial-specific IL-10R1-null mice revealed a remarkable increase in disease susceptibility associated with increased intestinal permeability. Together, these results provide novel insight into the crucial and underappreciated role of epithelial IL-10 signaling in the maintenance and restitution of epithelial barrier and of the temporal regulation of these pathways by IFN-γ.